2021
DOI: 10.1161/atvbaha.120.314641
|View full text |Cite
|
Sign up to set email alerts
|

Nonredundant Roles of Platelet Glycoprotein VI and Integrin αIIbβ3 in Fibrin-Mediated Microthrombus Formation

Abstract: Objective: Fibrin is considered to strengthen thrombus formation via integrin αIIbβ3, but recent findings indicate that fibrin can also act as ligand for platelet glycoprotein VI. Approach and Results: To investigate the thrombus-forming potential of fibrin and the roles of platelet receptors herein, we generated a range of immobilized fibrin surfaces, some of which were cross-linked with factor XIIIa and contained VWF-BP (von Willebrand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…GPVI is a key collagen and fibrin receptor on platelets (3-4 k copies per cell), which signals via a cascade of protein tyrosine kinases, leading to strong platelet activation [48,49]. GPVI interaction with subendothelial collagens induces arterial thrombus formation upon vascular injury, as confirmed in multiple in vivo studies with genetically modified mice and in microfluidics studies with mouse or human blood [50,51].…”
Section: Collagen Receptor Glycoprotein VI (Gpvi)mentioning
confidence: 93%
“…GPVI is a key collagen and fibrin receptor on platelets (3-4 k copies per cell), which signals via a cascade of protein tyrosine kinases, leading to strong platelet activation [48,49]. GPVI interaction with subendothelial collagens induces arterial thrombus formation upon vascular injury, as confirmed in multiple in vivo studies with genetically modified mice and in microfluidics studies with mouse or human blood [50,51].…”
Section: Collagen Receptor Glycoprotein VI (Gpvi)mentioning
confidence: 93%
“…Glass coverslips were coated overnight at 4 °C with Horm collagen (50 µg/mL) or plaque homogenate (0.5 mg/mL) before blocking with 10% BSA for 30 min in Hepes buffer (10 mM Hepes, 136 mM NaCl, 2.7 mM KCl, 2 mM MgCl 2 , 5.5 mM glucose, and 0.1% BSA), pH 7.45 [ 7 ]. Citrated whole blood, recalcified with CaCl 2 (7.5 mM) and MgCl 2 (3.75 mM), in the presence of PPACK (40 µM), was perfused for 7 min at 1000 s −1 [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…In vitro flow studies have shown that GPVI contributes to the stability of newly formed platelet aggregates on collagen at high shear through use of the blocking anti-GPVI Fab ACT017, which has more recently been named glenzocimab [ 4 ]. Since the activation of GPVI by fibrinogen is also dependent on integrin αIIbβ3, with the interplay of the two receptors driving platelet adhesion and activation [ 7 ]; this suggests that blocking signalling pathways common to both receptors may have a greater antithrombotic effect than blocking GPVI alone.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the genetic absence of GPVI does not abrogate clot retraction and recent studies show that GPVI and αIIbβ3 play complementary non-redundant roles. 89,90 GPVI may also have a physiologic role in inflammatory states, cancer and other acquired states in GT. 19,91 Platelet Proteome Some 40 years ago, McGregor et al 92 studied platelet membrane glycoproteins in GT by associating carbohydrate-specific or protein-specific labeling procedures with high-resolution two-dimensional gel electrophoresis.…”
Section: Gt Platelets and Fibrinmentioning
confidence: 99%
“…Nonetheless, the genetic absence of GPVI does not abrogate clot retraction and recent studies show that GPVI and αIIbβ3 play complementary non-redundant roles. 89 , 90 GPVI may also have a physiologic role in inflammatory states, cancer and other acquired states in GT. 19 , 91 …”
Section: Gt Platelets and Fibrinmentioning
confidence: 99%